2012
DOI: 10.1016/j.healun.2012.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and temporal trends among high-risk patients after lung transplantation in the United States

Abstract: Introduction: Although several studies have evaluated risk factors for mortality after lung transplantation (LTx), few studies have focused on the highest risk recipients. We undertook this study to evaluate the impact of high lung allocation scores (LAS), ventilator support, and extracorporeal membrane oxygenation (ECMO) support on outcomes after LTx. Methods: We retrospectively reviewed all LTx recipients in the United Network for Organ Sharing database. Primary stratification was by recipient acuity at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 21 publications
4
77
1
1
Order By: Relevance
“…Inappropriate patient selection and delayed deployment of ECMO technology have been significant predictors of poor patient outcomes (19,25). Unfortunately, there are no universally accepted guidelines available, and individual institutional practices dominate the decisions to bridge a patient on ECMO.…”
Section: Candidate Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inappropriate patient selection and delayed deployment of ECMO technology have been significant predictors of poor patient outcomes (19,25). Unfortunately, there are no universally accepted guidelines available, and individual institutional practices dominate the decisions to bridge a patient on ECMO.…”
Section: Candidate Selectionmentioning
confidence: 99%
“…Additionally, these patients should have a good nutritional status, moderate functional status and/or the perceived ability to rehabilitate while on ECMO support (19,27). Early consideration of ECMO in the management algorithm of these decompensating patients appears to result in more favorable outcomes.…”
Section: Candidate Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 However, with the advent of improved circuitry with lower complication rates, more experience with its use, and institution of ECMO earlier in a patient's course, recent studies have demonstrated significantly improved posttransplant outcomes. [38][39][40][41][42] The use of upperbody configurations help to facilitate rehabilitation, including ambulation, which has the benefit of maintaining-or even improving-physical conditioning and, consequently, transplant candidacy. 11,15,43,44 For select patients, ECMO may provide sufficient gas exchange to allow for the removal of invasive mechanical ventilation, further facilitating mobilization while eliminating the risks associated with invasive mechanical ventilation.…”
Section: Bridge To Lung Transplantationmentioning
confidence: 99%
“…As advances in lung transplantation continue to expand the donor pool (12)(13)(14) and improve outcomes in high-risk recipients (15), it is increasingly likely that transplant teams will need to address occult CAD in lung transplant candidates.…”
Section: Introductionmentioning
confidence: 99%